Cabaran membesarkan anak-anak autisme daripada perspektif ibu - Siti Marziah Zakaria,; Nor Shahirah Mat Tauhaid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The prevalence of Autism Spectrum Disorder (ASD) cases has been increasing worldwide. There are countless aspects of challenges faced by parents to bring up children with ASD. Parents of children with ASD are often reported to have higher stress in parenting compared to parents with normal children or children with other disabilities such as Down syndrome. Therefore, this study explored the challenges faced by mothers of children with ASD. Mothers whom were selected are the primary guardians and spend a lot of time nurturing these children. This qualitative study involved in-depth interviews with five (5) informants in Selangor. The thematic analysis identified the challenges faced by the mothers of children with ASD, which are the aspects of behavioral, financial and community acceptance. The findings showed that mothers to children with ASD encountered numerous complicated challenges which require the support of all parties to address those challenges. High support and compassionate understanding are really needed from the spouse, normal children, local communities, and government to alleviate their difficulties. Thus, the findings of this study hopefully will help various parties to understand the challenges faced by the mothers of children with ASD. It can also be the guiding principle in designing supportive programs and interventions for children with ASD as well as their parents.